Corps et genre des émotions dans l’hagiographie féminine au XIIIe siècle - Damien Boquet (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
Thirteenth-century Christian piety in the West was characterised by the rise of laypeople, more particularly women, and by a strong valuing of emotions in the devotional life. Historians have given little thought to the association between these two movements, as if they went together naturally. Yet, the spread of female affective mysticism was by no means predictable, since it was shaped by devotional models which had been devised for male monastic communities in the eleventh and twelfth centuries. Thus, what quickly became a female feature was not predetermined by any gendered logic. It is therefore necessary to write the history of the feminisation of affective piety from the end of the twelfth century onwards and look at the invention of a gendered stereotype that became increasingly forceful over the centuries.